Parent-Child Associations of Eating Habits According to Domains of Parental Physical Activity (Epi-Family Health Study) - De Moraes-Ferrari, G (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Background: The family environment and physical activity (PA) levels are known to influence the eating habits of children and adolescents, but it is unclear how different domains of parental PA can affect parent-child associations with eating habits. Methods: This study included 473 participants: 192 children and adolescents (aged between 5 and 17 years), 163 mothers, and 118 fathers. Parental PA was assessed in occupational, sports, and leisure-time/commuting domains. Children s and parents dietary intake was evaluated using a weekly food frequency questionnaire, covering healthy and unhealthy food groups. The mother-child and father-child associations were analyzed using multiple quantile regression. Results: Active mothers in occupational PA showed mother-child associations for fruits, vegetables, and dairy foods, whereas inactive mothers showed associations for fried foods and sweets. In the sports practice domain, active mothers showed mother-child associations for vegetables and red meat consumption, whereas active fathers showed associations for grains and salty snacks consumption. Active mothers in the leisure-time/commuting domain showed mother-child associations for fried foods and red meat consumption, while active fathers showed associations for fruits and salty snacks consumption. Conclusions: Mother-child associations were more consistent across PA domains than father-child associations. Overall, the healthy eating habits of physically active mothers were more strongly linked to the healthy eating patterns of their children.